THE IMPACT OF MINDFULNESS ON MOBILE PAYMENT TOOL USAGE - Humayrah, Saidatul (jfpublisher, 2023)
The application of mobile payment has not been spread to all Indonesians. However, there are many companies that have started to release and develop their own versions of mobile payment systems. Mobile payment systems, which are innovative forms of financial processing, connect customers and vendors online to complete transactions. The implication of mindfulness has been implicated in many mobile business intelligence technologies. Therefore, this research aims to determine the implications of mindfulness on mobile payment; to analyze hypotheses regarding the performance of mindfulness in affecting perceived usefulness, perceived ease of use, subjective norms, and attitudes. SEM applies with statistical methods in representing data and applies many models in achieving research objectives and resolving research problems. There were 251 data that represented active users who had experience in using mobile payments. The results of this research indicate that mindfulness has good exploratory strength in predicting consumer intention to adopt mobile payment, and it is proven that has a positive and significant impact on its four dimensions such as perceived ease of use, perceived benefits, and attitudes, which directly affect the intention to use.